Identification of two flavonoids antiviral inhibitors targeting 3C-like protease of porcine epidemic diarrhea virus - Li, Zhonghua; Zhu, Liangyun; Wang, Lu; Huang, Yizhi; Zhang, Yi; Zhao, Di; Wang, Lei; Yi, Dan; Hou, Yongqing; Wu, Tao (Frontiers in Microbiology, 2024)
Porcine epidemic diarrhea virus (PEDV) has caused severe devastating damage to the global pig industry in the past 20 years, creating an urgent demand for the development of associated medications. Flavonoids have emerged as promising candidates for combating coronaviruses. It is believed that certain flavonoids can directly inhibit the 3C-like protease (3CL pro ), thus displaying antiviral activity against coronaviruses. In this investigation, we applied a flavonoid library to screen for natural compounds against PEDV 3CL pro . Baicalein and baicalin were found to efficiently inhibit PEDV 3CL pro in vitro, with the IC50 value of 9.50 ± 1.02 μM and 65.80 ± 6.57 μM, respectively. A dDocking analysis supported that baicalein and baicalin might bind to the active site and binding pocket of PEDV 3CL pro . Moreover, both baicalein and baicalin successfully suppressed PEDV replication in Vero and LLC-PK1 cells, as indicated by reductions in viral RNA, protein, and titer. Further investigations revealed that baicalein and baicalin mainly inhibited the early viral replication of the post-entry stage. Furthermore, baicalein showed potential effects on the attachment or invasion step of PEDV. Collectively, our findings provide experimental proof for the inhibitory effects of baicalein and baicalin on PEDV 3CL pro activity and PEDV infection. These discoveries may introduce novel therapeutic strategies for controlling porcine epidemic diarrhea (PED).